An analysis of the role of costume and make-up in horror films: a case study of ‘the hills have eyes’ (2006) - Moyo, Sithabile (Midlands State University, 2018)
The study focused on analysing and finding out the importance of the role of costume and makeup in horror film making with particular focus on the horror film, ‘The Hills Have Eyes’ which was directed by Alexandra Aja in the year 2006. Findings of the study show how costume and makeup are important in film making and how they can also be used to enhance and convey film meaning in the horror genre. Theories like semiotics and audience reception were appointed in the study in order to show how costume and makeup are interpreted by the audience therefore suggesting that they should not be taken for granted as they communicate a message. The qualitative method was used as it gave the researcher an insight of what the audience thinks of costume and makeup and provided a platform for observation and personal analysis of the data they provided the researcher with.